Analisis Strategi Pemasaran Produk Bank Melalui Pemanfaatan Teknologi Informasi di PT. BSI Kc Simeulue - Sasmita, Maria; Hasanah, Uswah (Jurnal Manajemen Akuntansi (JUMSI), 2024)
This study aims to find out in detail about matters relating to the Marketing Strategy of bank products through the effective and comprehensive use of information technology at PT. BSI Simeulue Branch Office. The research method used in this study is a descriptive qualitative research method in the form of interviews with informants. The results of the research are in the form of interviews with BSI banks where researchers can say that by implementing several bank product marketing strategies and through the use of information technology at the bank it needs to be applied to customers so that there are no problems that are often experienced by customers when using the Mobile Banking application which often experience interruptions. Therefore it is necessary to have a marketing strategy for bank products through the use of information technology so that it can be carried out effectively. Analysis of the product marketing strategy carried out by the bank is to combine the components in the marketing mix, namely promotion strategy, product strategy, price strategy and service strategy. In addition, the constraints faced by customers of the BSI KC Simeulue bank will provide solutions in the form of directions and assistance customers so that they can solve the problems faced by these customers, the bank also provides the best service to its customers. the bank has done it to the maximum and then also uses information technology that can be understood by customers and according to customer needs.